Pseudomonas aeruginosa PAO1 exopolysaccharides are important for mixed species biofilm community development and stress tolerance - Periasamy, Saravanan; Nair, Harikrishnan A. S.; Lee, Kai W. K.; Ong, Jolene; Goh, Jie Q. J.; Kjelleberg, Staffan; Rice, Scott A. (Frontiers in Microbiology, 2015)
Pseudomonas aeruginosa PAO1 produces three polysaccharides, alginate, Psl and Pel that play distinct roles in attachment and biofilm formation for monospecies biofilms. Considerably less is known about their role in the development of mixed species biofilm communities. This study has investigated the roles of alginate, Psl and Pel during biofilm formation of P. aeruginosa in a defined and experimentally informative mixed species biofilm community, consisting of P. aeruginosa, Pseudomonas protegens and Klebsiella pneumoniae. Loss of the Psl polysaccharide had the biggest impact on the integration of P. aeruginosa in the mixed species biofilms, where the percent composition of the psl mutant was significantly lower (0.06%) than its wild-type parent (2.44%). In contrast, loss of the Pel polysaccharide had no impact on mixed species biofilm development. Loss of alginate or its overproduction resulted in P. aeruginosa representing 8.4% and 18.11%, respectively, of the mixed species biofilm. Dual species biofilms of P. aeruginosa and K. pneumoniae were not affected by loss of alginate, Pel or Psl, while the mucoid P. aeruginosa strain achieved a greater biomass than its parent strain. When P. aeruginosa was grown with P. protegens, loss of the Pel or alginate polysaccharides resulted in biofilms that were not significantly different from biofilms formed by the wild-type PAO1. In contrast, overproduction of alginate resulted in biofilms that were comprised of 35-40% of P. aeruginosa, which was significantly higher than the wild-type (5-20%). Loss of the Psl polysaccharide significantly reduced the percentage composition of P. aeruginosa in dual species biofilms with P. protegens (<1%). Loss of the Psl polysaccharide significantly disrupted the communal stress resistance of the three species biofilms. Thus, the polysaccharide composition of an individual species significantly impacts mixed species biofilm development and the emergent properties of such communities.